Abnormal Antithrombin III (Antithrombin III ‘Budapest’) as a Cause of a Familial Thrombophilia - Sas, G; Blaskó, G; Bánhegyi, D; Jákó, J; Pálos, L. Á (Thrombosis and Haemostasis, 1974)
A family with a high incidence of spontaneous thromboembolism has been investigated and those members affected were found to have significantly depressed levels of plasma and serum heparin cofactor activity; i.e., antithrombin III and anti-Xa activity. Further studies revealed that despite a marked diminution of antithrombin III activity in these patients measurement of antithrombin III by immunological techniques showed the levels to be normal. It is concluded that this anomaly represents a defect in the synthesis of the antithrombin III molecule. The abnormality appeared to be inherited but the mode of inheritance could not be determined with the available data.